2001
DOI: 10.1021/ie010076j
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of Hydrothermal Reactions 17. Kinetics of the Surface-Catalyzed Water−Gas Shift Reaction with Inadvertent Formation of Ni(CO)4

Abstract: The rate constants and Arrhenius parameters for the reaction of CO in H 2 O were determined at 230-270 °C and 27.4 MPa by the use of a titanium flow reactor with real-time detection by infrared spectroscopy through sapphire windows. These rate measurements appear to be the first below the critical temperature of water. The zeroth-order kinetics model produced an Arrhenius activation energy of 32 ( 3 kcal/mol, which is in the range of previously reported values at higher temperatures, but the preexponential fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Furthermore, no metal carbonyls were detected immediately downstream of the trap, and analysis of loosely bound carbon deposits upstream of the reaction zone (that is, perhaps carried away by the flow) (Figure 10) did not show the presence of nickel or iron. Thus the most likely source of the nickel (and iron) deposited in the preheating section is the formation of nickel (and iron) carbonyl in the presence of the stainless steel tubing immediately preceding the preheating section under the CO‐rich conditions as reported by Miksa and Brill 25. These carbonyls would then readily decompose in the hotter quartz tubing.…”
Section: Resultsmentioning
confidence: 78%
“…Furthermore, no metal carbonyls were detected immediately downstream of the trap, and analysis of loosely bound carbon deposits upstream of the reaction zone (that is, perhaps carried away by the flow) (Figure 10) did not show the presence of nickel or iron. Thus the most likely source of the nickel (and iron) deposited in the preheating section is the formation of nickel (and iron) carbonyl in the presence of the stainless steel tubing immediately preceding the preheating section under the CO‐rich conditions as reported by Miksa and Brill 25. These carbonyls would then readily decompose in the hotter quartz tubing.…”
Section: Resultsmentioning
confidence: 78%
“…The reactor cell and gas supply system have to be made from materials that do not interact with the reactant gases, which could lead to the formation of compounds that can contaminate the surfaces, e.g. Fe and Ni carbonyls generated from stainless steel (Sykes et al, 1993;Miksa & Brill, 2001). In our design these problems are avoided by coating all the materials in contact with the reactant gases with gold, and by using copper and brass for the gas lines and connections.…”
Section: Limitations Of Past Designsmentioning
confidence: 99%
“…By examining the water–gas shift reaction under hydrothermal conditions, Brill and Miksa35 have shown that the extremely toxic Ni(CO) 4 was formed by extraction of Ni from a slightly corroded 316 stainless steel (SS316) tube. These results are consistent with metals leaching from the reactor.…”
Section: Introductionmentioning
confidence: 99%